Quantifying the Forces Applied During Manually and Mechanically Assisted Calvings in Beef Cattle - Pearson, Jennifer M.; Thomsen, Charmaine; Kusler, Ann; Pajor, Edmund A.; Gurdita, Akshay; Ungrin, Mark David; Windeyer, M. Claire (Frontiers in Veterinary Science, 2020)
Dystocia is a leading cause of calf mortality, yet there is little available information quantifying the duration and forces applied to assisted deliveries. Objectives of this study were to: 1) develop a method to measure the magnitude and duration of various forces applied to a calf during calving assistance, and 2) quantify the forces applied to beef calves during manual or mechanical calving assistance. Twenty-five primiparous dams requiring calving assistance were enrolled. Calvings were assisted by manual (1 or 2 people pulling) or mechanical (calf extractor) delivery. A set of modified obstetric chains with integrated force measuring devices (Calving Assistance Force Logger; CAF-Log) were applied to the calf for delivery. The CAF-Log system was calibrated using known masses ranging from 25 kg to 200 kg in increasing increments of 25 kg. Duration of the assisted delivery and force parameters (peak force applied to one leg, peak force applied to both legs, cumulative force, and maximum jerk force) were described and assessed for their associations with method of delivery and ranch. Median duration was 112.6 seconds (IQR: 88.4-149.7) for manual and 312.6 seconds (IQR: 221.6-462.3) for mechanical deliveries. Mean peak force applied to one leg was 56.9 kg (SD: 22.9) for manual and 126.8 kg (SD: 48.2) for mechanical deliveries. Mean peak force applied to both legs was 95.4 kg (SD: 34.1) for manual and 188.6 kg (SD: 83.9) for mechanical deliveries. Median cumulative force was 178.3 kg min (IQR: 21.1-38.8) for manual and 380.6 kg min (IQR: 252.1-581.3) for mechanical deliveries. The maximum jerk force for manual deliveries was 36.6 kg/sec (IQR:21.1-38.8) and 77.2 kg/sec (IQR:60.9-97.1) for mechanical deliveries. An interaction occurred between ranch and method of delivery for peak force applied to one leg, peak force applied to both legs, and cumulative force. The CAF-Log system demonstrated that significantly greater forces were applied to mechanically delivered calves compared to manually delivered calves and could be used in future studies to investigate forces applied to a calf during calving assistance and their impacts on cow and calf wellbeing.